An assessment of the optimal air-side thermal-hydraulic performance of wavy-fin compact heat exchangers. (December 2018) - Qasem, Naef A.A.; Zubair, Syed M.
Highlights: The air-side thermal-hydraulic characteristics of wavy finned compact heat exchangers are presented. A robust method is introduced for the performance evaluation of different wavy-fin arrangements. Two benchmark geometries are proposed to compare the performance. Twenty-one new wavy-fin geometries are numerically studied. The performance results of 105 geometries are compared with the standard geometries. Abstract: An optimal assessment of heat transfer and friction power performance is investigated to address a robust method for facilitating performance evaluation of different wavy-fin arrangements. Two benchmark geometries are presented to compare the performance of all the reported wavy-fin arrangements with and without considering heat exchanger compactness. New 21 wavy-fin geometries are numerically studied to represent the unreported arrangements in the literature. The performance results of 105 geometries showed that the reference standard geometries of Kays and London could be used as benchmarks to evaluate the airside arrangements, with and without considering the compactness effect, respectively. Heat transfers versus friction power plots are found to be a useful approach for performance evaluation purpose. The surface GK2 is found to have the optimal thermal-hydraulic performance when comparing the heat exchanger compactness, whereas GI1 and GK1 might represent the geometries having optimal performances when neglecting the compactness importance.